2005
DOI: 10.1007/s00234-005-1345-0
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management for intracranial ruptured aneurysms in elderly patients: outcome and technical aspects

Abstract: The definition of an elderly person is debateable; however, age is a recognised negative prognostic factor for outcome after subarachnoid haemmorrhage, and the age cut-off of 60 years is accepted to define a high risk population. The goal of this article is to access the outcome in this precise population of patients that underwent endovascular treatment (EVT) after aneurysm rupture. Forty-two patients (mean age = 70.24) had 40 aneurysms located at the anterior circulation and nine at the posterior circulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 35 publications
1
19
2
Order By: Relevance
“…Twenty-three articles, 2,7,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] with 867 traditionally coiled and 273 balloon-assisted procedures met inclusion criteria for thromboembolism analysis, and 21 articles 10,12-31 with 993 traditionally coiled and 170 balloon-assisted procedure aneurysms were eligible based on inclusion criteria for perforation analysis. For the thromboembolism analysis, 12 articles contained cases exclusively treated by traditional-unassisted coiling, 6 articles described results for cases exclusively using balloon remodeling, and 5 reports provided relevant information for both unassisted and balloon remodeling cases, henceforth referred to as "mixed" reports.…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-three articles, 2,7,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] with 867 traditionally coiled and 273 balloon-assisted procedures met inclusion criteria for thromboembolism analysis, and 21 articles 10,12-31 with 993 traditionally coiled and 170 balloon-assisted procedure aneurysms were eligible based on inclusion criteria for perforation analysis. For the thromboembolism analysis, 12 articles contained cases exclusively treated by traditional-unassisted coiling, 6 articles described results for cases exclusively using balloon remodeling, and 5 reports provided relevant information for both unassisted and balloon remodeling cases, henceforth referred to as "mixed" reports.…”
Section: Incidencementioning
confidence: 99%
“…Ten articles 2,13,14,[16][17][18]22,23,26,28 provided sufficient information on the degree of initial occlusion. Follow-up information was available in 11 articles.…”
Section: Occlusion Analysismentioning
confidence: 99%
“…In many developed countries, SAH after of 70 years of age has been a frequent pathology. 1,2,15,16,21,23,30,32,33 Some authors believe that there is not a persistent increase of rupture risk. They argue that a maximum level is reached by the age of 70 years, and then a decrease is expected.…”
Section: Discussionmentioning
confidence: 99%
“…Procedural morbidity has also been decreasing. 14,15,[19][20][21][23][24][25] In addition, unlike open surgery, endovascular morbidity and mortality seem to be less dependent on a patient's age. 11,31,34 Our series demonstrated that endovascular coiling of elderly patients with unruptured intracranial aneurysms is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation